Marker-assisted selection strategies for developing resistant soybean plants to cyst nematode - Fernanda Abreu Santana; Martha Freire da Silva; Julierme Kellen Freitas Guimarães; Marcia Flores da Silva Ferreira; Waldir Dias Pereira; Newton Deniz Piovesan; Everaldo Gonçalves de Barros (Crop Breeding and Applied Biotechnology, 2014)
Resistant lines can be identified by marker-assisted selection (MAS), based on alleles of genetic markers linked to the resistance trait. This reduces the number of phenotypically evaluated lines, one of the limitations in the development of cultivars with resistance to soybean cyst nematode (SCN). This study evaluated the efficiency of microsatellites near quantitative trait loci (QTL) for SCN resistance, in the linkage groups (LG) G and A2 of soybean, for the selection of resistant genotypes in populations originated from crosses between the cultivars Vmax and CD201. The QTL of LG A2 was not detected in ‘Vmax’ (derived from PI 88788). In MAS, the microsatellites of LG G were efficient in selecting F6:7 families with resistance and moderate resistance to SCN race 3. The selection efficiency of the microsatellites Sat_168, Satt309 and Sat_141 was greater than 93%.